Extraction Separation of Gold in n-Propyl Alcohol- Ammonium Sulfate Aqueous Two-Phase System - Xiang, Pengzhi; Gao, Yuntao (Asian Journal of Chemistry, 2012)
The extraction behaviours of gold(III) in the n-propyl alcohol (PrOH)-ammonium sulfate aqueous two-phase extraction system were investigated. The amount of (NH4)2SO4 added, the initial volume of n-propyl alcohol and the acidity of the system are mainly factors that affect the formation and phase separation of the aqueous two-phase system. Gold(III) is found to be extracted into the n-propyl alcohol phase due to the formation of ion pair complex of [Au I4–·PrOH2+] in the presence of KI and in hydrochloric acid medium, an extraction rate of 99 % for gold can be achieved under optimized conditions. The proposed method has been applied to the separation of gold from large amount of base metals in synthetic sample and exhibits selectivity to gold(III).